8-Bit High Resolution Pipelined Analog-To-Digital Converter (ADC) With High Unity-Gain Bandwidth Operational Transconductance Amplifier (OTA) - Idros, Norhamizah (2019)
High unity-gain bandwidth operational transconductance amplifier (OTA) for high resolution 8-bit pipelined analog-to-digital converter (ADC) was designed to satisfy the differential non-linearity (DNL) of ±1 LSB and conversion time less than 20 /js. The resolution of pipelined ADC is limited by open-loop DC gain provided by the OTA that acts as the core element in developing the ADC. The existing design of folded cascode OTA does not has a high open-loop DC gain to maintain the resolution of 8-bit. The choice of folded cascode is the best suited architecture for high resolution switched capacitor application as compared to the other topology.